Determinants of Brand Equity of Services: A Verification Approach in the Banking Industry in Malaysia - Yasin, Norjaya Mohd.; Aziz, Norzalita Abd. (UI Scholars Hub, 2021)
This study attempts to verify the determinants of brand equity of services based on consumers’ perception of a banking service. The conceptual framework of this study is based on customer-based brand equity called the Brand Resonance model which comprises of six building blocks namely brand salience, brand performance, brand imagery, brand judgment, brand feelings and brand resonance. Factor analyses were conducted on all items measuring the six constructs and the results produced only five factors i.e brand salience, brand performance, brand judgments, brand feelings and brand resonance as the determinants of brand equity of services. Reliability test on all these factors produced satisfactory reliability coefficients. Correlation analysis was also conducted on the study variables and the results indicate that there are strong, positive and significant relationships between brand performance and brand judgment, and between brand performance and brand feelings. Strong, positive and significant relationships are also found between brand performance and brand resonance, between brand judgment and brand resonance as well as between brand feelings and brand resonance.